COMPARISON OF TARGET-CONTROLLED INFUSION AND MANUAL INFUSION OF PROPOFOL FOR COLONOSCOPY SEDATION IN ANESTHESIOLOGY TRAINEES - Dr H Radhika; M. Poorna Chandra; Y.Parthasaradhi Reddy; D Jothieswari (Journal of Population Therapeutics and Clinical Pharmacology, 2020)
Propofol is often used to sedate patients during colonoscopy, but its possible side effects on the heart and breathing are still worrisome. The aim of this study was to see if using target-controlled infusion (TCI) of propofol results in superior sedation quality for novice anesthesiology trainees than using manually controlled infusion (MCI). Initially, eighteen residents started training with TCI in one group and MCI in the other, finishing with TCI in their second month and MCI in their first. At the end of every month, the last two patients treated were picked for review. Both patients and doctors using the procedure gauged how much they were satisfied with the sedation, using a visual scale called VAS. Other important points we measured were heart rate (HR), mean arterial pressure (MAP), oxygen saturation (SpO_2) and how long recovery took. Baseline patient characteristics were the same in both the TCI and MCI groups. There was a clear difference in endoscopists’ satisfaction, with TCI receiving ratings of 81.3±7.2 compared to 74.2±9.5 for MCI (P=0.003), but no difference was found with patients. Hemodynamic stability in the TCI group was reflected by a lower maximum MAP and a higher minimum MAP, compared to the MCI group. In addition, the TCI group had better lowest SpO2 results. Studies have observed that people given propofol using TCI get better faster than those using MCI. Giving sedation via target-controlled infusion is considered more effective and safer for anesthesia residents performing colonoscopies.